Preparation of the pyridinium salts differing in the length of the N-alkyl substituent - Marek, Jan; Stodulka, Petr; Cabal, Jiri; Soukup, Ondrej; Pohanka, Miroslav; Korabecny, Jan; Musilek, Kamil; Kuca, Kamil (Molecules (Basel, Switzerland), 2010)
Quaternary pyridinium salts with chains ranging from C8 to C20 belong in the large group of cationic surfactants. In this paper, the preparation of such cationic surface active agents based on the pyridinium moiety and differing in the length of the N-alkyl chain is described. Additionally, HPLC technique was established to distinguish each prepared pyridinium analogue. This study represents universal method for preparation and identification of quaternary pyridinium detergents.
Keywords: pyridinové sloučeniny; Chromatography, High Pressure Liquid; Salts; Magnetic Resonance Spectroscopy; Pyridinium Compounds; magnetická rezonanční spektroskopie; vysokoúčinná kapalinová chromatografie; soli